AN ANALYSIS OF THE COOPERATIVE MAXIMS IN THE “OMAR” MOVIE - Suswanto Ismadi Megah; Kenthik D Wahyuni (CAHAYA PENDIDIKAN, 2018)
This study was aimed to analyze types of cooperative maxims in the” Omar” movie. In addition, this study could be considered as a language is a complex phenomenon whose meaning depends on where and when it is used in the “Omar”movie based on the interrogation between the Israeli soldier and the main character (Omar). This study used cooperative maxims  of Grice’s theory that  The cooperative principle was stated in the following way make your conversational contribution such as was required, at the stage at which it occurs, by the accepted purpose or direction of the talk exchange in which you were engaged. This study applied descriptive qualitative approach in analyzing of the data obtained. The data based on the transcription of the dialogue of the main character and the Israeli soldier. The data found was the maxim of quantity 16 %, maxim of quality 5%, maxim of relevant 47%, and maxim of manner 32 %. Therefore, in this study the most dominant was relevant maxims. Thus, the most frequently used was relevant maxims because the interrogation needed relevant to answer the interogerator.Keywords: Analysis, Cooperative Maxims and Omar Movie.